2016
DOI: 10.1186/s12879-016-1947-7
|View full text |Cite
|
Sign up to set email alerts
|

Low sensitivity of the tourniquet test for differential diagnosis of dengue: an analysis of 28,000 trials in patients

Abstract: BackgroundThe aim of this study was to evaluate the utility of the tourniquet test (TT) for dengue diagnosing. To our knowledge, no previous study with such a large sample, of this duration, with as many laboratory methods referenced, or relating the results of the TT to the 2009 WHO classification of severity has been conducted thus far.MethodsIn this study, we analyzed the records of 119,589 suspected dengue cases in a Brazilian city, with 30,670 confirmed cases. The Cohen’s Kappa test was applied to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Both leukopenia and leukocytosis have been described in dengue, depending on the timing during illness [ 11 , 29 , 30 ]. Our findings for the tourniquet test were consistent with other studies which showed a crucial role for this clinical parameter in predictive models for acute dengue illnesses [ 7 , 15 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Both leukopenia and leukocytosis have been described in dengue, depending on the timing during illness [ 11 , 29 , 30 ]. Our findings for the tourniquet test were consistent with other studies which showed a crucial role for this clinical parameter in predictive models for acute dengue illnesses [ 7 , 15 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…13 Similarly, a retrospective analysis of >28 000 tourniquet tests found no association between test results and final laboratory-confirmed diagnosis or dengue severity. 14 Increasing the diagnostic cut-off from >10 petechiae to >20 petechiae did not result in the expected decrease in sensitivity and increase in specificity. This poor biological correlation between dengue infection and capillary fragility may be underlying the test’s poor diagnostic performance.…”
Section: Clinical Diagnosismentioning
confidence: 86%
“…This poor biological correlation between dengue infection and capillary fragility may be underlying the test’s poor diagnostic performance. 13 Combined with practical considerations such as difficulty of interpretation in different skin colours and uncertainties around its positivity in other flavivirus infections, 14 it may be time to forgo the tourniquet test as a diagnostic criterion for dengue.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…The clinical variables that were added in WHO 2009, such as organ failure, may not necessarily represent a direct consequence of dengue, but of prior comorbidity or even iatrogenesis, as is the case of pulmonary distress due to hyperhydration . Even classical information adopted in both classifications may not express the clinical reality in dengue patients; the tourniquet test has been shown to have a low sensitivity in dengue diagnosis , and, since many DENV‐infected patients could be non‐febrile, fever may not be a reliable starting point criterion .…”
Section: Discussionmentioning
confidence: 99%